Numerical Approximation of a Linear Parabolic PDE (Dhaka University Journal of Science, 2013)
We study stability and convergence analysis of a finite difference approximation of a linear parabolic partial differential equation (PDE) in a periodic domain. In particular, we analyze consistency, stability and order of accuracy of a central space forward time scheme to solve the PDE. Dhaka Univ. J. Sci. 61(1): 59-63, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15097